Decision Supporting System Employee Performance Appraisal Narotama University with Simple Additive Weighting Method (SAW) - Subagyo, Hamzah Denny; Ariani, Ariani; Qoriani, Hersa Farida; Widodo, Gianto (Proceedings of the International Conference on Green Technology, 2017)
The quality of human resources is the most important thing to improve the productivity of an agency's performance. Narotama is one of the private university, located in Surabaya, East Java. As one of the major University in East Java, Narotama certainly has a lot of human resources or employees. To determine the level of performance and performance competence of human resources or employees in an agency, need a performance assessment. Performance appraisal is conducted to find out the achievement achieved by each employee by setting performance assessment criteria, in this study the criteria used are commitment, management, cooperation and work result. The criteria used are then processed into a decision support system using the appropriate method, in order to obtain the value of employee performance index. To determine a solution of the problem with the criteria used one of MCDM method is Simple Additive Weighting (SAW). Using secondary data in the form of 20 employees and 4 assessment criteria then processed by SAW method and classified by Arithmetic Interval method obtained result that is high performance employees as much as 4 keryawan, with performance is 7 employees and with enough performance as many as 9 employees